2021
DOI: 10.1109/jstars.2021.3093645
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based Target Detection and Classification When Sparse SAR Image Dataset is Available

Abstract: Synthetic aperture radar (SAR) is an earth observation technology that can obtain high-resolution image in allweather and all-time conditions, and hence has been widely used in civil and military applications. SAR target detection and classification are the key processes for the detailed feature information extraction of the interested target. Compared with traditional matched filtering (MF) recovered result, sparse SAR image has lower sidelobes, noise and clutter. Thus it will theoretically has better perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The reviewed techniques used for identification of synthetic images have limitations, some of which include, 1. The current techniques used for identifying synthetic images are not always effective in distinguishing between real and synthetic images [1][2][3]. Some of the techniques are based on statistical analysis of pixel-level features, which can be easily manipulated by sophisticated generators [4].…”
Section: Issues With Existing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed techniques used for identification of synthetic images have limitations, some of which include, 1. The current techniques used for identifying synthetic images are not always effective in distinguishing between real and synthetic images [1][2][3]. Some of the techniques are based on statistical analysis of pixel-level features, which can be easily manipulated by sophisticated generators [4].…”
Section: Issues With Existing Techniquesmentioning
confidence: 99%
“…Similar models [2][3][4] along with their functional nuances, application-specific advantages, contextual limitations, and deployment-specific future scopes are discussed in the next section of this text. Based on this discussion, it can be observed that existing models for synthetic image classification are either extremely sophisticated or incapable of scaling to multi-domain image sets.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the CAMP algorithm could achieve CFAR detection of sparse SAR images. Recently, Bi et al [33] used sparse SAR images as input data under a CNN architecture. This approach achieved a higher target classification performance than that obtained with the same network structure using MF SAR images as input.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, high-resolution and wide-swath imaging means that the complexity of the SAR system will increase dramatically. The proposal of the sparse SAR imaging technique has provided a new solution to this problem and has gradually become the main direction of SAR imaging [23]- [26]. Compared with matched filtering (MF)-based result, a sparse SAR image shows better performance with lower sidelobes and higher signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%